Effect of Water on Flow Fluctuation in River Flow - Okma Yendri (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2022)
River water fluctuations affect the amount of inundation that occurs. The study aims to obtain a cross-section of the river channel to drain runoff water so that the runoff due to maximum rainfall does not cause puddles. The Ketupak river flow cannot drain flow during the rainy season. Besides that, there is also a lot of sediment, garbage, stems and branches that interfere with the Ketupak river flow. Therefore, it is necessary to rearrange the river channel. From the results of calculations based on rainfall data, it is necessary to increase the cross-sectional area of the river.